A microstructural kinematic study of selected shear zones in the Hartbees River Thrust Belt, northeastern Namaqua Tectonic Province - Jackson, Christopher (Rhodes University, Faculty of Science, Department of Geology, 1992)
The Hartbees River Thrust Belt (HRTS) is a 40-60 km wide, southwest-vergent zone of complex structure, lithostratigraphy and high-grade metamorphism in the northeastern part of the mid-Proterozoic Namaqua Tectonic Province. The HRTS comprises the boundary zone separating the Bushmanland and Gordonia Subprovinces of the Namaqua Province. A knowledge of the movement histories of major ductile shear zones within the HRTS is fundamental to understanding the tectonic development of the belt, and Namaqua tectogenesis as a whole. In spite of this, no detailed microstructural kinematic studies have been attempted and the movement histories and age relationships of these shear zones have not been described in detail. This thesis represents a detailed microstructural kinematic study of a representative suite of orientated samples of mylonitic rocks, collected from five ductile shear zones within the HRTS. These shear zones include the Neusspruit Lineament, the Kakamas shear zone (KSZ), the Hugosput shear system (HSS), the Rozynenbosch-Ganzenmond shear zone (RGSZ) and the Graafwater shear system (GSS). Accepted modern methods of microstructural kinematic analysis were applied to samples of mylonite from these shear zones, in order to determine the precise orientation of the kinematic vectors, and the sense and relative ages of movements on each of the shear zones. Shear sense criteria, including composite SoC planar fabrics and shear band foliations, asymmetrical porphyroclast systems, mica-fish, oblique grain-shape and subgrain fabrics, asymmetrical microfolds, and the displacement of fractured rigid grains, together with a well-developed mylonite elongation lineation, conclusively indicate that SSW-directed thrusting occurred along the HSS, RGSZ, GSS and possibly along the Neusspruit Lineament, while normal, top-to-NE movements occurred on the Neusspruit Lineament, KSZ and HSS. Rare transposition criteria, and textural and paragenetic contrasts between syn-kinematic fabrics, strongly suggest that the phase of normal, top-to-NE movement seen in the northeastern HRTS shear zones is younger than the more widespread top-to-SW thrusting event. On the basis of mesoscopic structural criteria, SSW-directed thrusting is correlated with the D₂ deformation event in the HRTS. The mylonite zones have been refolded by ENE-SSW trending F₃ crossfolds, whose demonstrated coaxial relationship to the mylonite elongation lineation precluded reorientation of primary kinematic vectors. In the southwestern HRTS, primary thrust vectors have been reoriented by right-lateral, strike-slip shearing adjacent to the Pofadder Lineament during D₄. Simple shear dispersion of mylonite lineations related to normal movement, suggests that they too have been modified by D₄ shearing, and this constrains the timing of extensional movements to post-D₂ and pre- or syn-D₄. Syn-kinematic mineral assemblages, rheological criteria and the annealing states of the mylonites, provide insight into the thermotectonic evolution of the shear zones. A model is proposed in which the movement histories of shear zones within the HRTS are explained in terms of a typical orogenic cycle, involving crustal thickening by thrusting during a compressional orogenic phase, followed by collapse of the thickened crust during an extensional taphrogenic phase.
Keywords: Metamorphic rocks -- South Africa -- Northern Cape; Mylonite -- South Africa -- Northern Cape; Geology -- South Africa -- Northern Cape